An Updated Conceptual Model on the Pathogenesis of Bacterial Vaginosis. (1st August 2019) - Muzny, Christina A; Taylor, Christopher M; Swords, W Edward; Tamhane, Ashutosh; Chattopadhyay, Debasish; Cerca, Nuno; Schwebke, Jane R
Abstract: Bacterial vaginosis (BV) is the most common cause of vaginal discharge. It is associated with an increased risk of preterm delivery, pelvic inflammatory disease, and an increased risk of acquisition of sexually transmitted infections including human immunodeficiency virus (HIV). The epidemiology of BV supports sexual transmission. However, its etiology remains unknown. At the center of the debate is whether BV is caused by a primary pathogen or a polymicrobial consortium of microorganisms that are sexually transmitted. We previously published a conceptual model hypothesizing that BV is initiated by sexual transmission of Gardnerella vaginalis . Critics of this model have iterated that G. vaginalis is found in virginal women and in sexually active women with a normal vaginal microbiota. In addition, colonization does not always lead to BV. However, recent advances in BV pathogenesis research have determined the existence of 13 different species within the genus Gardnerella . It may be that healthy women are colonized by nonpathogenic Gardnerella species, whereas virulent strains are involved in BV development. Based on our results from a recent prospective study, in addition to an extensive literature review, we present an updated conceptual model for the pathogenesis of BV that centers on the roles of virulent strains of G. vaginalis, as well as Prevotella bivia and Atopobium vaginae . Abstract : This article provides an updated conceptual model for the pathogenesis of bacterial vaginosis, centering on the roles of virulent strains of Gardnerella vaginalis, as well as Prevotella bivia and Atopobium vaginae .